Analysis of Noise Intensity in the Work Environment as a Risk Factor for Increased Blood Pressure in Workers - Dwi Ayu Lestari Putri; Fitri Rokhmalia; Demes Nurmayanti; Halimah; Ambarwati (Public Health Research Development, 2024)
Farmers generally use rice mills as a tool to separate rice husks. The main driver of the rice milling machine is a diesel engine, which makes a lot of noise. Noise intensity that exceeds the threshold value can cause health problems for workers in the form of increased blood pressure. This study aimed to analyze the effect of noise intensity in the work environment on improving blood pressure. This research is an analytical observational study using a cross-sectional approach. The total population in this study was 40 workers. Proportionate Stratified Random Sampling is the sampling technique in this research, with a sample size of 37 respondents. Data collection techniques include interviews, measuring noise intensity, and measuring blood pressure. Data analysis used wilcoxon test and Spearman correlation test, where the test criteria for H0 are accepted if p > 0.05 and H0 is rejected at p < 0.05. Based on the results of research conducted at a rice mill in Driyorejo District, Gresik Regency, it can be concluded that there is a difference between blood pressure (systolic and diastolic) before and after work. There is an influence between noise intensity, work period, age, smoking habits, and hereditary history. There was no effect between exposure time and increased blood pressure.